Pengaruh Faktor Harga, Keamanan, Kemudahan, dan Kepercayaan Terhadap Perilaku Belanja Online Dimasa Pandemi Covid-19 - Listia Puji Rahayu; Ari Susanti (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
Shopping on online sites is one of the shopping systems of choice for many consumers today because the transaction process is easy and fast, as well as safer and does not cause bad effects that worry others, especially in the current conditions with the Covid-19 Pandemic. The purpose of this research is to analyze online shopping behavior in Indonesia, especially during the Covid-19 pandemic, by proving whether there is an influence of trust, convenience, security, and price factors on online shopping behavior or not. The research method uses quantitative methods. In this research, the size of the population is unknown or unlimited because of the large number of consumers who shop online. The size of the sample in this study amounted to 170 respondents, and identified using the Hair formula. The sampling technique used in this research is purposive sampling method which is limited by several criteria. The results obtained in this study are, Trust, and Price affect online shopping behavior in the future, while Ease and Security have no effect on online shopping behavior during the Covid-19 Pandemic